Pertanggungjawaban Hukum Terkait Pengelolaan Limbah B3 (Bahan Berbahaya dan Beracun) dalam Fasilitas Kesehatan - Suroto Suroto (Majelis: Jurnal Hukum Indonesia, 2024)
The aim of this research is to analyze how corporate criminal liability which is realized in the form of hospitals and/or emergency hospitals is linked to criminal acts of disposal of medical solid waste during the Covid-19 pandemic, and to determine the factors that influence this. creation of damage. implementing regulations. this criminal liability. The research results show that in this case the company and the administrative official who gave the order (manager) to commit a criminal act can be held criminally responsible. There are several factors that influence the realization of criminal responsibility, for example the lack of optimal supervision by law enforcement officers. Unclear provisions, particularly those relating to emergency hospital accommodation, require updating of the law.